Dietary protein intake is associated with better physical function and muscle strength among elderly women. Issue 7 (9th February 2016) - Isanejad, Masoud; Mursu, Jaakko; Sirola, Joonas; Kröger, Heikki; Rikkonen, Toni; Tuppurainen, Marjo; Erkkilä, Arja T.
Abstract: Dietary protein intake might be beneficial to physical function (PF) in the elderly. We examined the cross-sectional and prospective associations of protein intake of g/kg body weight (BW), fat mass (FM) and lean mass (LM) with PF in 554 women aged 65·3–71·6 years belonging to the Osteoporosis Risk Factor and Prevention Fracture Prevention Study. Participants filled a questionnaire on lifestyle factors and 3-d food record in 2002. Body composition was measured by dual-energy X-ray absorptiometry, and PF measures were performed at baseline and at 3-year follow-up. Sarcopaenia was defined using European Working Group on Sarcopenia in Older People criteria. At the baseline, women with higher protein intake (≥1·2 g/kg BW) had better performance in hand-grip strength/body mass (GS/BM) ( P =0·001), knee extension/BM ( P =0·003), one-leg stance ( P =0·047), chair rise ( P =0·043), squat ( P =0·019), squat to the ground ( P =0·001), faster walking speed for 10 m ( P =0·005) and higher short physical performance battery score ( P =0·004) compared with those with moderate and lower intakes (0·81–1·19 and ≤0·8 g/kg BW, respectively). In follow-up results, higher protein intake was associated with less decline in GS/BM, one-leg stance and tandem walk for 6 m over 3 years. Overall, results were no longer significant after controlling for FM. Associations were detected between protein intake and PF in non-sarcopaenic women but not in sarcopaenic women, except for change of GS ( P =0·037). Further, FM but not LM was negatively associated with PF measures ( P <0·050). This study suggests that higher protein intake and lower FM might be positively associated with PF in elderly women.